איך מפשטים 7 + 2 (4x - 3)?

איך מפשטים 7 + 2 (4x - 3)?
Anonim

תשובה:

# 8x + 1 #

הסבר:

להכפיל את התנאים ולהוסיף מונחים דומים:

# 7 + 2 (4x-3) = 7 + 8x-6 = 8x + 1 #

תשובה:

# 7 + 2 (4x-3) = 1 + 8x #

הסבר:

# 7 + 2 (4x-3) #

הפצת #2# על תנאי # (4x-3) #

#color (לבן) ("XXXX") ## = 7 + (2) (4x) - (2) (3) #

מבצע את הכפל

#color (לבן) ("XXXX") ## = 7 + 8x - 6 #

קיבוץ כמו מונחים

#color (לבן) ("XXXX") ## = (7-6) + (8x) #

ביצוע חיסור

#color (לבן) ("XXXX") ## = 1 + 8x #

תשובה:

להפיץ את #2#, ולאחר מכן לפשט.

הסבר:

# 7 + 2 (4x-3) #

להפיץ את #2#.

# 7 + 2 * 4x + 2 * -3 # =

לפשט.

# 7 + 8x-6 # =

# 8x + 1 #